2008
DOI: 10.1369/jhc.2008.952440
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Localization, and Binding Activity of the Ezrin/Radixin/Moesin Proteins in the Mouse Testis

Abstract: The ezrin, radixin, and moesin (ERM) proteins represent a family of adaptor proteins linking transmembrane proteins to the cytoskeleton. The seminiferous epithelium undergoes extensive changes in cellular composition, location, and shape, implicating roles of the membrane-cytoskeleton interaction. It remains unknown, however, whether the ERM proteins are expressed and play significant roles in the testis. In the present study, we examined the spatiotemporal expression of ERM proteins in the mouse testis by Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
(65 reference statements)
1
19
0
Order By: Relevance
“…After washing in phosphate buffer at 4˚C, the specimens were postfixed in 1% osmium tetraoxide for 2 h at 4˚C, washed repeatedly in distilled water, stained with 1% uranyl acetate for 30 min, dehydrated through a graded ethanol series and propylene oxide, and embedded in Glicidether (Selva Feinbiochemica, Heidelberg, Germany). Ultrathin sections were cut and mounted onto copper grids, stained with 1% uranyl acetate for 10 min and with Reynolds lead citrate for 5 min, and evaluated using an H7650 electron microscope (Hitachi, Tokyo, Japan) (25).…”
Section: Methodsmentioning
confidence: 99%
“…After washing in phosphate buffer at 4˚C, the specimens were postfixed in 1% osmium tetraoxide for 2 h at 4˚C, washed repeatedly in distilled water, stained with 1% uranyl acetate for 30 min, dehydrated through a graded ethanol series and propylene oxide, and embedded in Glicidether (Selva Feinbiochemica, Heidelberg, Germany). Ultrathin sections were cut and mounted onto copper grids, stained with 1% uranyl acetate for 10 min and with Reynolds lead citrate for 5 min, and evaluated using an H7650 electron microscope (Hitachi, Tokyo, Japan) (25).…”
Section: Methodsmentioning
confidence: 99%
“…Also, each of these four proteins has a unique function even they do share common functions (Table 1). Ezrin, radixin and moesin are found in the mouse testis, with ezrin associated with residual bodies, phagosomes and apical ES in the seminiferous epithelium [79]. Moreover, the expression of ezrin at the ES in the seminiferous epithelium of rat testes is highly stage-specific [80].…”
Section: Actin Binding Proteins (Abps)mentioning
confidence: 99%
“…Capping protein β3 is a component of the cytoskeleton calyx of the mammalian sperm head (von Bülow et al, 1997). Wakayama et al (2009) showed in mouse testis that radixin immunoreactivity was expressed in the apical cytoplasm of Sertoli cells from 1 wk through 2 wk postpartum and that radixin was bound to both actin and tubulin. Evidence indicated that radixin is involved in the maturation of Sertoli cells, through interaction with different sets of membrane proteins and cytoskeletal components.…”
Section: Effects On Cytoskeleton and Its Regulationmentioning
confidence: 99%